PERAN GURU DAN ORANG TUA DALAM PENANAMAN NILAI-NILAI MULTIKULTURAL PADA SISWA SD KELAS IV: DI KOTA MALANG - Yohana Yesica; Siti Ni’matul Fitriyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the roles of teachers and parents in instilling multicultural values ​​in fourth-grade students at SDN Merjosari 1 Malang City, as well as the forms of collaboration between the two. The method used was a qualitative case study approach through observation, interviews, and documentation. The results showed that teachers acted as designers, implementers, and role models, while parents instilled values ​​through habituation at home. Obstacles identified included students' exclusive attitudes and lack of communication. Reinforcement strategies were implemented through integrated learning and classroom dialogue. In conclusion, the synergy between teachers and parents is crucial in shaping students' tolerant, empathetic, and inclusive character.